2006
DOI: 10.1021/om0600543
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of the Bis-molybdenum(0) Trianion [1,3,6-{Mo(CO)3}-3,6-(μ-H)2-1,1,1-(CO)3-2-Ph-closo-1,2-MoCB9H7]3-:  Metal and Boron Vertex Substitution and Cluster Expansion

Abstract: Protonation of the 11-vertex bis-molybdenum−monocarbollide salt [NEt4]3[1,3,6-{Mo(CO)3}-3,6-(μ-H)2-1,1,1-(CO)3-2-Ph-closo-1,2-MoCB9H7] (1) with H[BF4]·OEt2 in the presence of CO and [NEt4]I results in molybdenum oxidation and cage expansion to yield 12-vertex [NEt4][2,2,2-(CO)3-8-OH-2-I-1-Ph-closo-2,1,8-MoC2B9H9] (5). In contrast, oxidation of 1 with Ag[BF4] in the presence of CNBut similarly results in metal oxidation but also in cage substitution to give 11-vertex [1,1,1,1,3-(CNBut)5-2-Ph-closo-1,2-MoCB9H8] … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 39 publications
(44 reference statements)
0
2
0
Order By: Relevance
“…In attempting to redress the monocarbollide/dicarbollide imbalance, we had been limited essentially to 12-vertex {MCB 10 } species, as the {CB 10 } carboranes were by far the most readily accessible . Recently, however, there has been a resurgence in monocarborane chemistry, initiated by Brellochs, which has led to straightforward procedures for the synthesis of monocarboranes with 7–10 vertices. , We have exploited the potential of this breakthrough to prepare a number of metal−monocarbollide species in the 9–11-vertex range, several of which have displayed chemistry not seen in their larger cluster relatives. In one such system 9- and 10-vertex {FeCB 7 } and {Fe 2 CB 7 } species were synthesized, but a trace third product defied identification for some time.…”
Section: Introductionmentioning
confidence: 99%
“…In attempting to redress the monocarbollide/dicarbollide imbalance, we had been limited essentially to 12-vertex {MCB 10 } species, as the {CB 10 } carboranes were by far the most readily accessible . Recently, however, there has been a resurgence in monocarborane chemistry, initiated by Brellochs, which has led to straightforward procedures for the synthesis of monocarboranes with 7–10 vertices. , We have exploited the potential of this breakthrough to prepare a number of metal−monocarbollide species in the 9–11-vertex range, several of which have displayed chemistry not seen in their larger cluster relatives. In one such system 9- and 10-vertex {FeCB 7 } and {Fe 2 CB 7 } species were synthesized, but a trace third product defied identification for some time.…”
Section: Introductionmentioning
confidence: 99%
“…Although at first such studies were essentially limited to 12-vertex {MCB 10 } species derived from the corresponding long-known {CB 10 } carboranes, recent developments in the synthesis of smaller monocarboranes have allowed access to sub-icosahedral metal−monocarbollide complexes and thence to their polymetallic derivatives. Among the latter class, we have prepared {MCB 9 } (M = Re, Mn, Mo), {Co 2 CB 9 }, {MCB 8 } (M = Fe, Co 7 ), {FeCB 7 }, and {M 2 CB 7 } (M = Fe, Co 7 ) species and have demonstrated that many of these clusters add an additional metal center upon treatment with a suitable cationic moiety.…”
Section: Introductionmentioning
confidence: 99%